Identification on Histamine Content and Histamin-Forming Bacteria of Boiled Badeng Slender Tuna - Yuliana Syalviana Fatuni; Ruddy - Suwandi; Agoes Mardiono Jacoeb (Jurnal Pengolahan Hasil Perikanan Indonesia, 2014)
Pindang is a semi-dried product which relatively short lasting products. Due to the rapid formation of histamine and bacterial enzyme activities contained in the fish, it is necessary to study and identify the histamine levels either on fresh tuna or in its pindang. This study aims to analyze histamine and histamine-forming bacteria in processed pindang tuna (A. rochei). Fresh tuna (A. rochei) was obtained from TPI Cisolok Palabuhanratu. The fish was processed according to pindang badeng method (20% salt added, boiled for 8 hours). The product then stored at room temperature and observed for 0,8,16,24 and 32 hours. Analysis were conducted through chemical (histamine and TVB) and microbiological test (TPC, identification of bacteria, histamine levels in bacteria). The results showed that the stored pindang for 32 hours can reactivate the production of histamine and increase their levels significantly. This is consistent with the increase on the value of TVB and TPC in pindang products. Six types of histamine-forming bacteria found on pindang tuna that are P. vulgaris, H. alvei, M. Morganii, E. aerogenes, K. oxytoca, K. pneumoniae. Activity test results showed that K. pneumoniae and H. alvei form the highest and the lowest levels of histamine formation respectively.Keywords: Histamine, bacterial, boiled tuna (Auxis rochei)